МАКТАБГАЧА ТАЪЛИМ МУАССАСАСИ ПЕДАГОГ ХОДИМЛАРИ ФАОЛИЯТИДА КРЕАТИВЛИК СИФАТЛАРИ - Гайназарова, Г. (FAN va JAMIYAT, 2018)
In this article, on the basis of scientific analysis, issues, conditions and peculiarities of the formation and development of the qualities of creativity among teachers of pre-school educational institutions in the process of reforms implemented in the education system of our country have been studied from theoretical and practical positions.